The Impact of the 2021 Military Coup on Myanmar’s Foreign Military Policy - Tyas, Wening (LPPM Universitas PGRI Sumatera Barat, 2024)
On February 1, 2021, the military junta launched a coup against Myanmar's civilian government. According to circulating reports, the coup occurred due to the military's dissatisfaction with the performance of the civilian government, especially regarding alleged fraud in Myanmar's 2020 elections. In response to this conflict, the purpose of this study is for the international community to convey a negative attitude by imposing sanctions and embargoes—one of which is the arms embargo issued by the UN General Assembly in 2021. The methodology used in this study is a case study approach. The data used in this study are secondary data in various forms, including official documents (such as government reports, agreements, and NGO analysis), media reports (news articles and opinion pieces), and academic literature (research articles, books, and theses on state identity). Facing this negative response, Myanmar is looking for new 'strategic partners' to ensure the sustainability of various vital sectors, especially the military sector. The data shows that, after the 2021 coup, Myanmar has continued to develop cooperative relations with Russia, especially in terms of arms procurement. This phenomenon raises the following research question: How did the 2021 military coup affect Myanmar’s decision to make Russia its strategic military partner? Using Wendt’s concept of state identity, the novelty of this study analyzes the impact of various factors—such as image, international norms and culture, and domestic politics—on the formation of Myanmar’s state identity, and how this newly formed identity affects Myanmar’s interests and foreign policies.